In vitro evaluation of cytotoxic and genotoxic effects of Di(2-ethylhexyl)-phthalate (DEHP) on European sea bass (Dicentrarchus labrax) embryonic cell line. (April 2019) - Molino, Chiara; Filippi, Silvia; Stoppiello, Gerardo Antonio; Meschini, Roberta; Angeletti, Dario
Abstract: Marine litter is extensively distributed in the marine environment, and plastic debris, of which litter is mostly composed, can be a major source of pollutants. Among them, Di(2-ethylhexyl)-phthalate (DEHP) is the most abundantly used plastic additive, and it has been reported to affect biochemical processes both in humans and wildlife; however, studies on its toxicological effects on marine organisms are still scarce. In this survey, we studied the cytotoxic, genotoxic, and mutagenic effects of DEHP in European sea bass embryonic cell line (DLEC) by applying specific in vitro tests. Results showed a significant decrease in cell viability starting at 0.01 mM of DEHP after 24 h together with a significant increase in apoptosis and necrosis, morphological changes and cell detachment. Consistently, we detected a moderate increase in DNA strand breaks from 0.02 mM, and a dose-dependent increase in of micronucleus frequency from 0.01 mM, accompanied by a significant inhibition of cell proliferation, which suggested a possible aneugenic effect of this phthalate. Our results demonstrate that in vitro exposure to DEHP had a dose-dependent cytotoxic and genotoxic effects in DLEC cell line, encouraging further investigation into its effects in in vivo and/or ex vivo cell systems of marine organisms. Highlights: DEHP cytotoxicity and genotoxicity testing in European sea bass embryonic cell line DEHP decreased cell viability and inhibited cell proliferation. DEHP caused a low primary DNA damage and a higher induction of micronuclei. Results suggest an anueugenic effect of DEHP on the sea bass embryonic cell line.